103k views
2 votes
Guys need help its surd one

5 \sqrt{3 / 2 \sqrt{3 - √(2) } }


1 Answer

1 vote

Answer:

Explanation:


\displaystyle \Large \boldsymbol{} 5\cdot \sqrt{3:2\sqrt{3-√(2) } } =\\\\\\ 5\cdot \sqrt{\frac{3}{2\sqrt{3-√(2) } } \cdot \frac{2\sqrt{3+√(2) } }{2\sqrt{3+√(2) } } } = \\\\\\5\cdot \sqrt{\frac{6\sqrt{3+√(2) } }{4\cdot √(9-2) } } =5\sqrt{\frac{6\sqrt{3+√(2) } }{2√(7) } }

But if the condition would be like this


\displaystyle \Large \boldsymbol{} 5\cdot \sqrt{3:2\sqrt{3-\boldsymbol2√(2) } } =\\\\\\5\cdot \sqrt{\frac{3}{2\cdot \sqrt{\underbrace{2+1-2√(2) \cdot √(1) }_((√(2) -1)^2) } }} =\\\\\\5\cdot \sqrt{(3)/(2\cdot (√(2)-1) ) } } = \\\\\\ 5\cdot \sqrt{(3)/(2(√(2)-1 )) \cdot (√(2) +1)/(√(2)+1 )} =5 \sqrt{(3)/(2(2-1)) } =\boxed{5√(1,5) }

User Nullman
by
5.4k points